Non-coherent demodulation algorithm of MSK based on differential composite - Wenbiao TIAN; Peng WANG; Guosheng RUI; Yang ZHANG (Tongxin xuebao)
An algorithm of MSK demodulation based on differential composite grid was proposed. The MSK differential composite grid was constructed by phase deflection, and the optimal path in the composite grid was selected by comparing the likelihood function value to compensate the phase error of the Doppler frequency offset. Theoretical analysis and simulation show that the performance of the algorithm was still close to the theoretical lower bound of the MSK non-coherent demodulation error rate when the phase error caused by the Doppler frequency offset was of the order of 10− 1rad magnitude. The algorithm extends the range of MSK demodulation anti-Doppler frequency offset, and is superior to similar algorithm in complexity and decision delay time, slightly higher than 1 symbol differential algorithm corresponding value, which provides a new means for demodulation of MSK under Doppler frequency offset.